OPTIMALISASI PERPUSTAKAAN SEKOLAH DALAM MENINGKATKAN MINAT BACA SISWA DI MINU SUMBERPASIR PAKIS MALANG - Izza Nuriyah Ilmi; Anwar Sa’dullah; Mohammad Afifulloh (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
The library is a learning resource in schools and can be used as a place to study other than in the classroom. However, it is not easy to invite students to visit the library frequently due to several factors. The problems that exist at MINU Sumberpasir Malang, one of which is in the condition of the library which is still less attractive, the reading books are still minimal and the location of the books is still not neat so students are still not interested in visiting it. The location of this research is at Madrasah Ibtidaiyah Nahdotul Ulama' Sumberpasir Pakis Malang. In this study, the researcher used a qualitative approach, with the type of case study research. The results of the research carried out are the condition of the MINU Sumberpasir library room in general can be said to be feasible and comfortable, for library services at MINU Sumberpasir Pakis Malang itself has provided a fairly good service. In terms of students' reading interest themselves, it is quite good, as for strategies to increase reading interest, there are methods and strategies that are interconnected to provide increased reading interest in students. Keywords: Optimization, Library, reading interest